(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The current research aims to reveal the nature of the relationship between performance on the mental imagery test and performance on the shape fluency test among a sample of students from the Faculties of Education and Fine Arts at the University of Damascus, using the mental imagery test prepared (Roland B Goay, 1986), which consists of 30 shapes, and a test of Figural Fluency prepared by Nadia Muhammad Abdel Salam, Suleiman Al-Khudari Al-Sheikh, and Anwar Muhammad Al-Sharqawi, 1996. The test contains three sections: the first section is the decoration test, the second section is the adding details test, and the third section is the test. Symbols: The sample number was 252 male and female students, including 131 male and female students from the College of Fine Arts, in addition to 121 male and female students from the College of Education, including 121 males and 131 females. The differences in the performance of the sample members on the tests of Figural Fluency and mental imagery were due to the variables of gender and college, and the most important results were as follows: • There is a statistically significant correlation of 0.451 between the research sample members’ scores on the mental visualization test and their scores on the shape fluency test. • There are statistically significant differences at 0.01 between the averages of students of the College of Education and students of the College of Fine Arts on the mental visualization test in favour of students of the College of Fine Arts. • There are statistically significant differences at 0.01 between the averages of the College of Education students and the College of Fine Arts students on the shape fluency test in favour of the College of Fine Arts students. • There are no statistically significant differences between the averages of males and females on the mental visualization and shape fluency tests.